PERAN KEPALA DESA DALAM PENYELESAIAN KONFLIK AGRARIA LOKAL (STUDI KASUS DI DESA SERA TENGAH KECAMATAN BLUTO) - Vicry, Jaysal; Maisaroh, Siti; Mafluhah, Mafluhah; Rohman, Habibur (Governance, 2025)
As stated in Law Number 6 of 2014 on Village, the Village Head is required to maintain peace and order in the village community, so that if a conflict occurs in the community, it is the responsibility of the Village Head to resolve it. This study aims to analyze the role of the Chief of Village in resolving agraria conflicts, in this case land disputes in Sera Tengah Village, Bluto District. The research method uses a qualitative approach with data collection techniques using interviews and participatory observation. The results of this study are that the role of the Chief of Village is very significant in resolving agraria conflicts in Sera Tengah Village. The role of the Chief of Village, which is his responsibility, can resolve agraria conflicts without continuing to the court process. The resolution mechanism is in the form of Complaints to the Chief of Village or village apparatus, problem analysis, data/evidence analysis, mediation and ends with the decision process issued by the chief of village with the disputing parties witnessed directly by the Sera Tengah Village Apparatus.